ANTIOXIDANT ACTIVITY, POLYPHENOLS AND FLAVONOIDS OF Coffea arabica FROM FIVE PERUVIAN REGIONS - Suárez Cunza, Silvia (2021)
Coffee prepared in various ways contains phenols and flavonoids with antioxidant activity and health benefits. Peruvian coffee has little information on its antioxidant properties. The objectives were to evaluate the total antioxidant capacity in vitro and the content of total phenols and flavonoids; then compare the coffees from the valleys of Chanchamayo (Junín), Tutumbaro (Ayacucho), Oventeni (Ucayali), Jaén (Cajamarca) and Quillabamba (Cusco). Samples were prepared by 2% w/v infusion. Soluble solids were determined by refractometry and apparent density by gravimetry; total phenols with the Folin-Ciocalteau reagent and flavonoids according to Zhishen. The total antioxidant capacity was evaluated using DPPH, ABTS. + and FRAP, the results are expressed as Trolox equivalent antioxidant capacity (TEAC) and as Ascorbic Acid equivalent antioxidant capacity (AAEAC). Total phenol results were 2.8–3.0 mmol GAE/g, flavonoids were 135–155 μmol ChE/g. The results of TEAC with DPPH were between 44–52 mg/g and between 41–50 mg/g for AAEAC; with ABTS between 55–62 mg TEAC/g and between 47–52 mg AAEAC/g; There was a significant difference (p <0.05) for the DPPH and ABTS between Junín and Cusco. In the FRAP, between 493 and 540 μmol EqFeSO4/g. There were no significant differences. It is concluded that the aqueous extracts of the roasted and ground grains of Coffea arabica from the five valleys have an antioxidant effect in vitro in association with the content of total phenols and flavonoids, the difference in antioxidant capacity is not relevant. This behavior is comparable with results reported in the international literature.